2022
DOI: 10.1002/aocs.12579
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency preparation of standard grade γ‐tocopherol and its antioxidant activity

Abstract: Natural standard grade γ-tocopherol is of great interest due to its good antioxidant activity and special pharmacological functions. This study separated and purified γ-tocopherol from mixed tocopherols using eco-friendly and low toxicity solvents. γ-Tocopherol (0.28 g) was obtained per performance with a purity of (98.89 AE 0.68)% and a recovery rate of (93.23 AE 0.89)%. The purification conditions were as follows: elution solvent n-hexane/ethyl acetate 94.5:5.5 (v/v), sample load 0.5 g, a column height to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, the removal efficiency of silica gel for α‐tocopherol was not satisfactory, which may be related to the differences in the chromatographic properties of the tocopherol homologues in the silica gel column. α‐Tocopherol contains three methyl groups on the chromanol ring, whereas two methyl groups and one methyl group are present for γ‐tocopherol and δ‐tocopherol, respectively [39], resulting in a relatively high hydrophobicity of α‐tocopherol and a weak interaction with the polar surface of silica gel.…”
Section: Resultsmentioning
confidence: 99%
“…However, the removal efficiency of silica gel for α‐tocopherol was not satisfactory, which may be related to the differences in the chromatographic properties of the tocopherol homologues in the silica gel column. α‐Tocopherol contains three methyl groups on the chromanol ring, whereas two methyl groups and one methyl group are present for γ‐tocopherol and δ‐tocopherol, respectively [39], resulting in a relatively high hydrophobicity of α‐tocopherol and a weak interaction with the polar surface of silica gel.…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin E (tocopherol), as a good natural antioxidant, plays an important role in the nutritional composition of maize and the nutritional evaluation of fatty acids [ 74 ]. The results showed that when the content was less than 100 mg/100 g [ 75 ], the antioxidant activity of γ-tocopherol in vitro was better than that of α-tocopherol and δ-tocopherol [ 76 ]. In addition, γ-tocopherol has been proven to inhibit and promote cancer or increase the expression of tumour suppressor genes by interfering with the signaling pathway of cell cancer [ 77 ].…”
Section: Resultsmentioning
confidence: 99%